MULTI CRITERIA DECISION ANALYSIS AND ITS APPLICATION TO TECHNOLOGY SELECTION - Fenita Rosaria (Jurnal Teknobisnis, 2005)
Recently, environmental technologies are widely available to prevent pollution from industrial activities. The term Best Available Techniques (BAT) refers to technologies that can be used to overcome certain environmental problems. The selection of the right technology for pollution prevention involves a complicated process. Not only technical and economic aspects, but also environmental aspect should be considered as well. However, environmental aspect is difficult to quantify due to uncertainty in the real value of the environment. The aim of this study is to develop a framework for decision making process that incorporates the three aspects: technical, environmental, and economic in selecting the best technology which is relevant to a certain textile industry. One multi criteria decision analysis tool, Analytic Hierarchy Process (AHP), is used in this study to help decision maker in a textile industry to compare and rank three alternative technologies: substitution of mineral oil, pre-wetting process and compact spinning technology. Substitution is the most feasible option having benefit/cost (B/C) ratio 2.154, followed by compact spinning with B/C ratio 0.879. The result shows that AHP is capable to quantify both qualitative and quantitative criteria to aid decision maker in comparing several options and determining the best option.